2016 포뮬러 형태의 자작자동차 설계 및 제작 - 김진석(Jin-Seok Kim); 신대수(Dae-Soo Shin); 신민수(Min-Soo Shin); 김성걸(Seong Keol Kim) (한국생산제조학회지, 2017)
In 2016, a handmade vehicle called to the VF-3 was designed and manufactured as a formula typed car. Prior to manufacturing and assembly, the impact attenuator was analyzed through ANSYS LS-DYNA, and the results were applied to the VF-3. The dynamical performance of the VF-3, such as the acceleration and circling simulations, was also assessed through MSC-ADAMS. The results were applied and compared after the Korean Society of Automotive Engineers (KSAE) competition. There was only a 0.8 s difference in the acceleration test. In order that the frame was not twisted by thermal deformation, Argon-TIG welding was used and a zig was designed. Another zig was designed to have the exact position for the hardpoints in the suspension system. Most of the parts were made with aluminum 7050 for reduced weight. The VF-3 won the third prize in the 2016 KSAE Student Handmade Vehicle competition.